Breeding systems, gene flow and level of genetic differentiation in plant populations - Rocha, Oscar (Lankesteriana: International Journal on Orchidology, 2016)
Genetic variation and its distribution among plant populations are primarily determined by their breed- ing system and the level of gene flow among them (Bawa et al. 1985, Bawa et al. 1990, Rocha & Aguilar 2001b). It is well known that mating systems influence the amount, as well as the distribution of the genetic variation within and among populations (Wright 1921, Stebbins 1950, 1957, Hamrick et al. 1991).